1997
DOI: 10.1021/jp9723933
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Nature of the Active Sites in CoMo Hydrotreating Catalysts. An EXAFS Study of the Reaction with Selenophene

Abstract: The genesis of sulfur vacancies on sulfided (Co)Mo/Al 2 O 3 catalysts was studied with EXAFS at the reaction temperature (673 K) in a H 2 and H 2 /thiophene gas atmosphere. For Mo no significant changes in the sulfur coordination were observed for either the Co-promoted or the unpromoted sample. The experiments indicated that in Co-promoted Mo/Al 2 O 3 vacancies are primarily formed on the Co atom. The sulfur coordination of the cobalt changed from 6.0 to 5.2 upon reduction with H 2 , followed by a slight incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 46 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…64,65 Taking into account all the first Co neighbors of Mo atoms in the model interface, a value of 2.758 Å is found in complete agreement with those determined by EXAFS. The structural model interface found herein would lead to similar Co-Mo distances as those obtained experimentally using X-ray absorption techniques.…”
Section: Electronic Propertiessupporting
confidence: 77%
“…64,65 Taking into account all the first Co neighbors of Mo atoms in the model interface, a value of 2.758 Å is found in complete agreement with those determined by EXAFS. The structural model interface found herein would lead to similar Co-Mo distances as those obtained experimentally using X-ray absorption techniques.…”
Section: Electronic Propertiessupporting
confidence: 77%
“…The extended X-ray absorption fine structure (EXAFS) Ni-Mo and Co-Mo distances 56,57 are, respectively, 2.85 and 2.80 Å, and our Ni e,IV -Mo i,VI and Co e,IV -Mo i,VI computed distances are 2.76 and 2.79 Å, respectively, in good agreement with experimental data. The Ni c,IV -Mo i,VI , Co c,IV -Mo i,VI , Ni c,IV -Mo i,VI and Co c,IV -Mo i,VI distances also agree favorably with experiment.…”
Section: Resultssupporting
confidence: 80%
“…The most relevant geometrical parameters of the Ni 3 Mo 13 S 32 and Co 3 Mo 13 S 32 clusters are shown in Table 1. These values are compared to experimental data 56,57 and calculations of Raybaud et al 18 using DFT with periodic boundary conditions. The periodic approach does not show the distortion in the metallic edge present in the cluster model, namely, a slightly distorted local structure around the Ni c,IV and Co c,IV atoms (Table 1).…”
Section: Partition Of the Electron Densitymentioning
confidence: 99%
“…On the other hand, the Zn atom is charged positively as the Mo e,IV atom of the unreplaced cluster, and the Zn-Mo c,IV distance becomes longer (it should be mentioned that the local structure around Mo c,IV atoms might be distorted a little due to "edge artifact of the cluster-model"). For Cr, the structure and charges are similar to those of [4,21,22], indicating that the local distances around replaced atoms can be simulated well by using clusters with the simple edge termination. Raybaud et al [11] have also reported similar Co-Mo i,VI distances from 2.75 to 2.89 Å for two-fold CUS Co atoms with and without sulfur adsorption on other CUS sites.…”
Section: Geometry Optimization Of Replaced Xmo 15 S 32 Clustersmentioning
confidence: 67%
“…Startsev has proposed that the adsorption and activation of thiophene occur on Ni or Co atoms [3]. Leliveld et al [22] have investigated reaction of selenophene (a structural analogue of thiophene) on CoMo-sulfided catalysts by EXAFS; they have showed that selenophene is chemisorbed on the Co atom, hydrogenated, and desorbed as H 2 Se at 473 K. The adsorption of thiophene on a cluster has been studied starting from an upright configuration on a replaced atom, because we have found previously [14] that the calculated vibrational frequencies for the upright configuration correspond well to the IR spectrum for thiophene adsorbed on the sulfided Mo catalyst [15].…”
Section: Adsorption Of Thiophene On Replaced Clustersmentioning
confidence: 99%